Pengaruh country of origin ( asal negara produk ) harga dan kualitas terhadap keputusan pembelian alat tulis - Habiburrahman Habiburrahman; Mulyadi Raf; Syilvia Kartika (Jurnal Dinamika Manajemen, 2019)
One of effect the open market is the entry of products originating from abroad, which directly or indirectly can affect the local product of the country. The object of this research is the stationery product, the stationery is chosen because it is one of the products that closest to daily student activities as respondents to this study. The purpose of this study is to determine the effect of country of origin price and product quality influence partial or simultaneous in purchasing decision of stationery, and to know what most variable influential to purchasing stationery. Analyze appliance used in this research is Multiple Linear Regression by using the analysis tool is the result of this study is the variable of country of origin and quality partially have a positive and simultaneous influence on the purchasing decision of stationery. While the price variable partially have a positive but not significant effect on the purchasing decision of stationery, if tested simultaneously then country of origin variable of price and quality have positive and significant effect to decision of stationery. For the most influential variable in the purchase of stationery in this study is the quality variable. Based on this research the stationery company besides having to continuously improve the quality of its products also enter the country identity because country of origin which owned by consumer can influence consumer purchasing decision.